Techno-economic analysis of low carbon hydrogen production from offshore wind using battolyser technology - Jenkins, Brian; Squires, David; Barton, John; Strickland, Dani; Wijayantha, Upul K. G.; Carroll, James; Wilson, Jonathan; Brenton, Matthew; Thomson, Murray (MDPI, 2022)
A battolyser is a combined battery electrolyser in one unit. It is based on flow battery technology and can be adapted to produce hydrogen at a lower efficiency than an electrolyser but without the need for rare and expensive materials. This paper presents a method of determining if a battolyser connected to a wind farm makes economic sense based on stochastic modelling. A range of cost data and operational scenarios are used to establish the impact on the NPV and LCOE of adding a battolyser to a wind farm. The results are compared to adding a battery or an electrolyser to a wind farm. Indications are that it makes economic sense to add a battolyser or battery to a wind farm to use any curtailed wind with calculated LCOE at £56/MWh to £58/MWh and positive NPV over a range of cost scenarios. However, electrolysers, are still too expensive to make economic sense.
Keywords: battolyser; electrolysis; energy storage; wind generation; stochastic modelling; NPV